Analisis Tindak Tutur Pada Film Komang Karya Naya Anindita - Manurung, Rafency; Siregar, Junifer; Silitonga, Immanuel Doclas Belmondo; Sirait, Jumaria; Tambunan, Marlina Agkris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze speech acts in the dialogue of the film Komang directed by Naya Anindita using a pragmatic approach, particularly J.L. Austin’s theory. The focus includes three types of speech acts: locutionary, illocutionary, and perlocutionary acts. This research employs a descriptive qualitative method, with data collected through observation and documentation of the film’s dialogues.The results show that the film contains various speech acts reflecting language use in social interaction. Locutionary acts convey information, illocutionary acts express intentions such as requesting and expressing feelings, and perlocutionary acts produce effects on the hearer. These speech acts contribute to the development of the storyline, characterization, and relationships between characters.Thus, language in the film functions not only as communication but also as social action with meaning and impact.